Home enteral nutrition after esophagectomy for esophageal cancer: A systematic review and meta-analysis. Issue 36 (4th September 2020) - Liu, Li; Wang, Yu-cui; Liu, Qian-wen; Zhong, Jiu-di; Li, Jin-bo; Wu, Xiao-dan; Qin, Hui-ying
Abstract: Background: Not only has the placement rate of enteral feeding tubes during operations for esophageal cancer increased, but also has number of patients who choose to continue enteral feeding at home instead of removing the feeding tube at discharge. The impacts of home enteral nutrition (HEN) after esophagectomy in esophageal cancer patients are analyzed. Methods: A systematic review was conducted in accordance with PRISMA and Cochrane guidelines. English and Chinese databases, including PubMed, Embase, Web of Science, The Cochrane Library, Scopus, CBM, CNKI, and Wan Fang were searched from inception to December 7, 2019. Randomized controlled trials evaluating the short-term outcomes of HEN following esophagectomy in cancer patients were included. The risk of bias of the included studies was appraised according to the Cochrane risk of bias tool. The summary of relative risk/weighted mean difference (WMD) estimates and corresponding 95% confidence interval (95% CI) were calculated using fixed- and random-effects models. Results: Nine randomized controlled trials involving 757 patients were included in the meta-analysis. Compared with oral diet, HEN was associated with significantly increased body weight (WMD 3 kg, 95% CI 2.36–3.63, P < .001), body mass index (WMD 0.97 kg/m 2, 95% CI 0.74–1.21, P < .001), albumin (WMD 3.43 g/L, 95% CI 2.35–4.52, P < .001), hemoglobin (WMD 7.23 g/L, 95% CI 5.87–8.59, P < .001), and total protein (WMD 5.13 g/L, 95% CI 3.7–6.56, P < .001). No significant differences were observed in prealbumin and gastrointestinal adverse reactions. Physical (WMD 8.82, 95% CI 6.69–10.95, P < .001) and role function (WMD 12.23, 95% CI 2.72–21.74, P = .01) were also significantly better in the HEN group. The nausea/vomiting (WMD −5.43, 95% CI −8.29 to −2.57, P = .002) and fatigue symptoms (WMD −11.76, 95% CI −16.21 to −7.32, P < .001) were significantly reduced. Appetite loss (WMD −8.48, 95% CI −14.27 to −4.88, P = .001), diarrhea (WMD −3.9, 95% CI −7.37 to −0.43, P = .03), and sleep disturbance (WMD −7.64, 95% CI −12.79 to −2.5, P = .004) in the HEN group were also significantly less than the control group. Conclusions: HEN improved nutrition status, physical and role function, and reduced nausea/vomiting, fatigue, appetite loss, diarrhea, and sleep disturbance compared with an oral diet in esophageal cancer patients postsurgery. HEN did not increase adverse reactions. Abstract : Supplemental Digital Content is available in the text